DEVELOPMENT OF INTERACTIVE DIGITAL PICTURE STORY MEDIA TO ENHANCE FIFTH-GRADE STUDENTS' READING LITERACY IN MENGWI DISTRICT - Ni Kadek Ayu Dewi Sukartini; Ni Ketut Diah Damayanti; Ni Nyoman Kurnia Wati (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This research aimed to develop an interactive digital picture story-based learning media that is valid, practical, and effective in enhancing reading literacy among fifth-grade elementary students in Cluster 2 of Mengwi District. Using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation), the study involved 28 fifth-grade students and one classroom teacher at SD Negeri 2 Mengwi. Data were collected through expert validation sheets assessing content, language, and visual design; teacher and student practicality questionnaires; and reading literacy tests (pretest–posttest). Validity testing yielded an overall score of 88.6%, categorized as